Perbuatan dan Azab Neraka dalam Hadis: Analisis Tematik dan Etika Eskatologis - Nur Asyifa; Muhammad Alif (Al-Mu'tabar, 2025)
This study analyzes the relationship between human actions and the threat of hellfire punishment from the perspective of the Hadiths of Prophet Muhammad (peace be upon him). Using a thematic (maw??‘?) approach, this research explores authentic Hadiths that explicitly describe various reprehensible acts and the corresponding forms of hellish punishment warned as their consequences. The study employs the method of takhrij to verify the authenticity of the chains of transmission (sanad), followed by matan analysis to uncover the ethical messages and spiritual dimensions embedded within. Findings indicate that the majority of hellfire threats are rooted in violations of the rights of fellow humans (?uq?q al-‘ib?d)—such as lying, corruption, injustice, and other social transgressions—rather than ritual violations. This article emphasizes that the eschatological understanding in Hadiths is not merely dogmatic, but serves as a moral character-building mechanism.